Evaluation of tongue/mandible volume ratio in children with obstructive sleep apnea - Kavita Hotwani; Krishna Sharma; Arpan Jaiswal
ABSTRACT Objective: The present study was an attempt to investigate tongue/mandible volume ratio in children, using volumetric magnetic resonance imaging (MRI) for early screening and to aid in treatment planning. Methods: Volumetric evaluation of tongue volume/mandible volume ratio (TV/MV ratio) in children with obstructive sleep apnea (OSA) using MRI was carried out retrospectively on available DICOM MR images of children in the age group of 10-14 years. MRI image records of patients diagnosed with OSA were obtained from interventional radiology department records, at Sharad Pawar Dental College and Hospital (Datta Meghe Institute of Medical Sciences, Nagpur/India). The age, gender, height and weight of the subjects were retrieved from patient database and registered. For the control group, available MRI images of healthy subjects without OSA were retrieved. Body mass index (BMI) was also calculated using the height and the weight present in the records. Measurements from MR images were made using DICOM image processing software. Soft tissue and bony structure segmentation was performed by manual tracing. The tongue volume and mandible volume were directly computed using the software. The tongue volume/mandible volume ratio (TV/MV) was generated using the above values and expressed as a percentage for both groups. Results: The difference between OSA group and control group with respect to TV/MV ratio was found to be highly significant at 0.05 level of significance. There was no significant correlation between BMI and TV/MV ratio in OSA group (p= 0.451) as well as in control group (p= 0.094). Conclusion: TV/MV ratio may be an appropriate variable to evaluate the risk of OSA, representing the balance between skeletal morphology and soft tissue morphology in craniofacial complex.